ChemInform Abstract: One‐Pot Synthesis of Organophosphate Monoesters from Alcohols. Issue 27 (13th June 2013) - Lira, Lucas M.; Vasilev, Dimitri; Pilli, Ronaldo A.; Wessjohann, Ludger A.
Abstract A reactive phosphorylated trichloroacetimidate, prepared in situ, is treated with alcohols to form organophosphate monoesters as ammonium salts which are used in biological processes.